Stock Market Asymmetries: A Copula Diffusion - Denitsa Stefanova (Tinbergen Institute, 2012)
The paper proposes a model for the dynamics of stock prices that incorporates increased asset co-movements during extreme market downturns in a continuous-time setting. The model is based on the construction of a multivariate diffusion with a pre-specified stationary density with tail dependence. I estimate the model with Markov Chain Monte Carlo using a sequential inference procedure that proves to be well-suited for the problem. The model is able to reproduce stylized features of the dependence structure and the dynamic behaviour of asset returns.
urn:NBN:nl:ui:31-1871/39446
Keywords: C11; C51; C58; 330; tail dependence; multivariate diffusion; Markov Chain Monte Carlo; Kapitaleinkommen; Börsenkurs; Prognoseverfahren; Markovscher Prozess; Monte-Carlo-Methode; Theorie